2022
DOI: 10.3390/jcm11030679
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Neonatal Characteristics of Children with Prader-Willi Syndrome

Abstract: Objective: Prader-Willi syndrome (PWS) is a rare genetic syndrome with a wide spectrum of clinical features in early life. Late diagnoses are still present. We characterized the perinatal and neonatal features of PWS, compared them with those of healthy newborns and assessed the prenatal and neonatal differences between the genetic subtypes. Design: A cohort study in children with PWS. The prevalence of variables was compared with healthy infants (PLUTO cohort) and to population statistics from literature. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
4
13
0
Order By: Relevance
“…These results are consistent with those of previous reports from other countries. [9][10][11][12] Our study showed that patients with UPD had a higher maternal age than patients with deletions. Maternal UPD is mainly caused by trisomy rescue and gamete complementation.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These results are consistent with those of previous reports from other countries. [9][10][11][12] Our study showed that patients with UPD had a higher maternal age than patients with deletions. Maternal UPD is mainly caused by trisomy rescue and gamete complementation.…”
Section: Discussionmentioning
confidence: 50%
“…Although the clinical characteristics of perinatal and neonatal patients with PWS have been reported, [9][10][11][12] there are no reports on the clinical characteristics of perinatal and neonatal patients with PWS in Japan. Therefore, this study aimed to evaluate these clinical characteristics in patients with PWS in Japan and to compare the findings of the two most common genetic subtypes: deletion and UPD.…”
mentioning
confidence: 99%
“…Many patients in our group had a Prader–Willi-like phenotype (i.e., hypotonia, hyperphagia, overweight/obesity), but not all. The neonatal phenotype of TS14 was quite similar to that of PWS, but our patients with TS14 had a lower birth weight than is generally seen in patients with PWS [ 39 ]. The body composition profile of patients with TS14 with a high FM% and low LBM is more similar to that of patients with PWS [ 30 ] than to that of those with SRS [ 40 ].…”
Section: Discussionmentioning
confidence: 88%
“…However, our patients had a normal to high FM%, which is very rare in young children with SRS [ 40 ]. Unlike in PWS and SRS, a large number of patients did not require tube feeding after birth (47%) and those with tube feeding required it for days instead of several weeks to months as in PWS [ 39 ] or even years as can occur in SRS [ 11 ]. Other distinctive characteristics of TS14, such as precocious puberty, a disharmonic intelligence profile and specific behaviors, are uncommon or completely lacking in PWS and SRS.…”
Section: Discussionmentioning
confidence: 99%
“…PWS results from the lack of expression of the PWS region (locus q11-q13) on the paternally derived chromosome 15 [ 1 , 2 , 4 ] due to a paternal deletion of the PWS region (50–75%), a maternal uniparental disomy (mUPD; 20–44%), an imprinting defect (<5%) or translocation (<1%) [ 5 , 6 , 7 , 8 ]. Most cases (>99%) can be easily detected using DNA methylation analysis to detect deletions or abnormal methylation of the PWS region [ 9 ].…”
Section: Introductionmentioning
confidence: 99%